Enhanced Supercapacitor Performance of Polyindole Nanocomposites via Optimized 2D SnS2 Nanosheet Integration: Structural, Optical, and Electrochemical Investigations - Beyazay, Emre; Ozdemir, Zeynep Guven; Karabul, Yasar (WILEY, 2026)
This study addresses the growing demand for sustainable energy storage by developing high-performance supercapacitor electrodes based on polyindole (PIn) nanocomposites integrated with 2D SnS2 nanosheets. Using cost-effective and scalable hydrothermal and chemical oxidative polymerization methods, the electrodes were fabricated via spin coating. Structural (XRD, FE-SEM, and SEM), optical (UV-Vis), and electrochemical (CV, GCD) analyses reveal that the 3% SnS2-doped composite exhibits a specific capacitance of 188 F/g and an energy density of 25.04 Wh/kg, outperforming pure PIn and many previously reported PIn-based systems. The layered morphology of SnS2 enhances ion transport and faradaic activity, making this composite a promising candidate for environmentally friendly hybrid energy storage applications.
Keywords: batteries and fuel cells; conducting polymers; nanoparticles, nanowires and nanocrystals; VOLUMETRIC CAPACITIVE PERFORMANCE; ELECTRODE MATERIAL; FACILE SYNTHESIS; COMPOSITE; Polymer Science